2020
DOI: 10.1093/immadv/ltaa001
|View full text |Cite
|
Sign up to set email alerts
|

Protective low-avidity anti-tumour CD8+ T cells are selectively attenuated by regulatory T cells

Abstract: Regulatory T cells (Treg) play a major role in the suppression of protective anti-tumour T cell responses. In the CT26 BALB/c murine model of colorectal carcinoma, Tregs differentially suppress responses to two characterised CD8+ T epitopes, AH1 and GSW11, which results in an absence of detectable IFN-γ producing GSW11-specific T cells in the spleen and lymph nodes of tumour challenged mice. Activation of GSW11-specific T cells correlates with protection against tumour progression. Here we show that GSW11-spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…We have previously described the evolution of tumor-specific CD8 + T cell response in BALB/c mice 7–22 days after subcutaneous implantation of autologous CT26 colorectal tumors. 15 CD8 + T cells of multiple specificities were primed in the tumor-draining lymph nodes (t-DLN), and as the tumor progressed, the ratio of effector to exhausted phenotypes detectable in the t-DLNs decreased. At the tumor site, the CD8 + T cell response largely focuses on two epitopes of the murine leukemia virus glycoprotein gp70 (AH1 and GSW11) which together account for 60%–90% of CD8 + TILs between days 14 and 22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described the evolution of tumor-specific CD8 + T cell response in BALB/c mice 7–22 days after subcutaneous implantation of autologous CT26 colorectal tumors. 15 CD8 + T cells of multiple specificities were primed in the tumor-draining lymph nodes (t-DLN), and as the tumor progressed, the ratio of effector to exhausted phenotypes detectable in the t-DLNs decreased. At the tumor site, the CD8 + T cell response largely focuses on two epitopes of the murine leukemia virus glycoprotein gp70 (AH1 and GSW11) which together account for 60%–90% of CD8 + TILs between days 14 and 22.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the IFNγ response of GSW11-specific CD8 + T cells was revealed when CT26 was inoculated subcutaneously in Treg-depleted recipients, which correlated well with protection and involved the selective expansion of low avidity clonotypes. 15 CT26 is a heavily utilized preclinical model in immuno-oncology studies and has been critical for the preclinical development of several PD-1 antibodies where numerous reports have shown it to be moderately responsive to anti-PD-1. 16 17 Therefore, we set out to investigate the involvement of the GSW11-specific responses in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work on KRAS-G12D specific TCRs suggests that TCRs with affinities in the high nM to low μM range are most effective for anti-tumour function, in line with a 'goldilocks' zone for TCR affinities [2,7,27,28]. However, other models have suggested that low avidity TCRs are superior to higher avidity [29]. More investigations into the affinities of effective anti-tumour TCRs are required to understand the desired biophysical properties of TCRs to be used in the clinic.…”
Section: Discussionmentioning
confidence: 98%
“…Low-affinity T cells can still contribute productively to anti-tumor immunity if properly activated, but how to activate these T cells in vivo and exploit this potential pool of anti-tumor T cells is unclear ( 48 ). Several approaches to augment expansion of low-affinity T cells have been reported including inhibition of Src homology region 2 domain–containing phosphatase-1 or depletion of T regulatory T cells ( 72 , 73 ). Critically, any such approaches must affect only antigen-specific T cells, as broader T cell activation could lead to autoimmune side effects ( 74 , 75 ).…”
Section: Discussionmentioning
confidence: 99%